2018
DOI: 10.1101/396994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Staufen2 mediated RNA recognition and localization requires combinatorial action of multiple domains

Abstract: Throughout metazoans, Staufen (Stau) proteins are core factors of mRNA localization particles. They consist of three to four double-stranded RNA binding domains (dsRBDs) and a C-terminal dsRBD-like domain. Mouse Staufen2 (mStau2) like Drosophila Stau (dmStau) contains four dsRBDs. Existing data suggest that only dsRBDs 3-4 are necessary and sufficient for mRNA binding.Here, we show that dsRBDs 1 and 2 of mStau2 bind RNA with similar affinities and kinetics as dsRBDs 3 and 4. While RNA binding by these tandem d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…To test if a regulatory circuit built around Staufen and Egalitarian also acts on other transcripts, we analyzed the localization and composition of the anterior localizing bicoid mRNPs (Fig 6A; Berleth et al, 1988), a known target of Staufen (Ferrandon et al, 1994) and a likely target of Egalitarian (Dienstbier et al, 2009;Ferrandon et al, 1994) . As previously reported, bicoid mRNPs may also contain multiple mRNA copies (Ferrandon et al, 1994;Heber et al, 2019;Trovisco et al, 2016 and Fig 6B and S5B), similar to oskar mRNPs. We found that the relative amount of Staufen-associated bicoid mRNPs is largely independent of RNA copy number (Fig 6B).…”
Section: Localization Of Bicoid Mrna Is Regulated By Staufen and Egalitariansupporting
confidence: 84%
See 2 more Smart Citations
“…To test if a regulatory circuit built around Staufen and Egalitarian also acts on other transcripts, we analyzed the localization and composition of the anterior localizing bicoid mRNPs (Fig 6A; Berleth et al, 1988), a known target of Staufen (Ferrandon et al, 1994) and a likely target of Egalitarian (Dienstbier et al, 2009;Ferrandon et al, 1994) . As previously reported, bicoid mRNPs may also contain multiple mRNA copies (Ferrandon et al, 1994;Heber et al, 2019;Trovisco et al, 2016 and Fig 6B and S5B), similar to oskar mRNPs. We found that the relative amount of Staufen-associated bicoid mRNPs is largely independent of RNA copy number (Fig 6B).…”
Section: Localization Of Bicoid Mrna Is Regulated By Staufen and Egalitariansupporting
confidence: 84%
“…Quantifying oskar mRNA copy number by smFISH (Fig S3A ), we found that the fraction of Staufen-associated oskar mRNPs in the oocyte increased as a function of oskar mRNA content, and the increase was substantially more pronounced during stage 9 than in earlier stages of oogenesis (Fig 3B). During stage 9, not only the likelihood of Staufen association but also the relative levels of Staufen -as reported by the normalised Staufen-GFP signal -increased and this increase was highly linear (Fig 3B' and Fig S3C), similarly to what we reported for overexpressed Staufen and mammalian Stau2 (Heber et al, 2019). Prior to the onset of oskar localization, Staufen levels showed no scaling with oskar mRNA content of the mRNPs (Fig 3B').…”
Section: Staufen Dissociates Egalitarian From Oskar Mrnps In the Oocytesupporting
confidence: 81%
See 1 more Smart Citation
“…Notably, BD3 and RBD4 regulate STAU1 RNA-binding activity (Wickham et al, 1999) and RBD4-TBD is involved in ribosome association (Luo et al, 2002). We now show that STAU1 association with spindles requires the N-terminal region that contains RBD2, a domain devoid of RNA-binding activity in vitro (Wickham et al, 1999), although we do not exclude the possibility that RBD2 could bind RNA in vivo as reported for the paralogue protein STAU2 (Heber et al, 2019). This result indicates that STAU1 RNAbinding and ribosome-binding activities are not involved in spindle association.…”
Section: Discussionmentioning
confidence: 60%
“…Koh et al have shown involvement of dynamics at the dsRNA-dsRBD interface where the diffusion of dsRBDs of TRBP along pre-miRNA favor its cleavage to the miRNA:miRNA* duplex by Dicer -an RNase III enzyme (Koh et al, 2013). Heber et al have recently compared binding affinities and binding stabilities of various dsRBDs in a multi-domain protein for RNA-recognition in Drosophila Staufen protein (Heber et al, 2019). Fareh et al have shown that the recognition of target dsRNA by TRBP involves dual binding modes to discriminate between the target dsRNA and other cellular dsRNAs to which protein is exposed (Fareh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%